2014
DOI: 10.1007/s00216-014-8000-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence imaging to track real-time armadillo promoter activity in live Drosophila embryos

Abstract: We established a method for bioluminescence imaging (BLI) to track real-time gene expression in live Drosophila embryos. We constructed a transgenesis vector containing multiple cloning sites and enhanced green-emitting luciferase (ELuc; Emerald Luc), a brighter and pH-insensitive luciferase for promoter analysis. To evaluate the utility of BLI using an ELuc reporter together with an optimized microscope system, we visualized the expression pattern of armadillo (arm), a member of the Wnt pathway in Drosophila,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Wnt signaling in segment polarity is well studied, but many additional functions have been observed 37 . Recently 38 , reported that intestinal formation during embryo development was disrupted in embryos treated with ionomycin, an inhibitor of Wnt/β-catenin signaling. By coupling optogenetics with live imaging, we observed a similar defect in intestinal development in Arm-CRY2-mCh expressing arm XM19 mutant embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling in segment polarity is well studied, but many additional functions have been observed 37 . Recently 38 , reported that intestinal formation during embryo development was disrupted in embryos treated with ionomycin, an inhibitor of Wnt/β-catenin signaling. By coupling optogenetics with live imaging, we observed a similar defect in intestinal development in Arm-CRY2-mCh expressing arm XM19 mutant embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling in segment polarity is well studied, but many additional functions have been observed 36 . Recently, 37 reported that intestinal formation during embryo development was disrupted in embryos treated with ionomycin, an inhibitor of Wnt/β-catenin signaling. By coupling optogenetics with live imaging, we observed a similar defect in intestinal development in Arm-CRY2-mCh expressing arm XM19 mutant embryos.…”
Section: Discussionmentioning
confidence: 99%
“…This is convenient for three-dimensional image reconstruction by light sectioning. Accordingly, we constructed transgenic Drosophila melanogaster carrying an armadillo (a member of the segment polarity gene) promoter and luciferase fusion gene [31]. Figure 10 shows three-dimensional images of armadillo promoter activity from insular larva of transgenic flies reconstructed from 11 sectionalized images (front and slant views).…”
Section: Three-dimensional Imaging Of Drosophila Larvamentioning
confidence: 99%
“…In our previous studies, we optimized an optical system using a short-focal-length imaging lens for bioluminescence microscopy and performed bioluminescence imaging of single live cells expressing the luciferase gene using a conventional CCD camera [20,21]. This system is commercially available now and has been widely used for gene expression analysis in chronobiology [22][23][24][25][26][27][28], neurobiology [29,30], developmental biology [31], medical research [32][33][34][35], signal transduction analysis [36][37][38], molecular interaction [39][40][41], and radiation biology [42,43]. Accordingly, in this study, we describe the concept of bioluminescence microscopy adopting a short-focal-length imaging lens and present several representative applications, including a three-dimensional analysis, to demonstrate the advantages of the short-focal-length imaging lens system.…”
Section: Introductionmentioning
confidence: 99%